2012
DOI: 10.1111/j.1742-4658.2012.08730.x
|View full text |Cite
|
Sign up to set email alerts
|

pH‐dependent structural conformations of B‐phycoerythrin from Porphyridium cruentum

Abstract: B-phycoerythrin from the red alga Porphyridium cruentum was crystallized using the technique of capillary counter-diffusion. Crystals belonging to the space group R3 with almost identical unit cell constants and diffracting to 1.85 and 1.70 Å were obtained at pH values of 5 and 8, respectively. The most important difference between structures is the presence of the residue His88a in two different conformations at pH 8. This residue is placed next to the chromophore phycoerythrobilin PEB82a and the new conforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 44 publications
3
26
0
Order By: Relevance
“…Phycoerythrobilins were linked covalently with each of aCys82, aCys139, bCys82 and bCys158, whereas a phycourobilin was linked doubly to bCys50 and bCys61. The presence of chromophores at these sites is highly conserved among PEs of which structures have been reported (Lundell et al 1984;Chang et al 1996;Ritter et al 1999;Contreras-Martel et al 2001;Camara-Artigas et al 2012). Taken these observations together, we concluded that dulse PE has structural characteristics common to other PEs.…”
Section: D Structures Of Dulse Phycoerythrinsupporting
confidence: 77%
See 1 more Smart Citation
“…Phycoerythrobilins were linked covalently with each of aCys82, aCys139, bCys82 and bCys158, whereas a phycourobilin was linked doubly to bCys50 and bCys61. The presence of chromophores at these sites is highly conserved among PEs of which structures have been reported (Lundell et al 1984;Chang et al 1996;Ritter et al 1999;Contreras-Martel et al 2001;Camara-Artigas et al 2012). Taken these observations together, we concluded that dulse PE has structural characteristics common to other PEs.…”
Section: D Structures Of Dulse Phycoerythrinsupporting
confidence: 77%
“…; Camara‐Artigas et al . ). Taken these observations together, we concluded that dulse PE has structural characteristics common to other PEs.…”
Section: Resultsmentioning
confidence: 97%
“…2A, Table 1). This value is in the middle between the value reported from size exclusion chromatography (272 AE 5 kDa) [12] and the widely accepted molecular weight for B-PE of~240 kDa [10,24], thus we attribute these peaks to the intact B-PE protein complex. Peaks were also observed at the lower m/z region corresponding to a protein complexes of 39 304 Da and 117 955 Da and at higher m/z corresponding to a complex of 528 kDa in size.…”
Section: Resultsmentioning
confidence: 61%
“…In contrast, the γ subunit is predicted to contain four bilin subunits; two PEB and two phycourobilins (PUB) . Physiologically, B‐PE is thought to reside as a large macromolecular complex composed of two [(αβ) 2 ] 3 hexamers and a single γ polypeptide . The specific inter‐ and intramolecular interactions present within the complex are crucial for B‐PE's role in light transmission.…”
Section: Introductionmentioning
confidence: 99%
“…According to González-Ramírez et al (2014), changes in the state of protonation on amino acid residues have a large effect on changes in spectral properties of PB. Spectroscopic changes due to low pH may be the result of differences in the state of protonation in the propionate group in the structure of PEB or in the aspartate residues that bind to the group (Camara-Artigas et al, 2012).…”
Section: Pece Stability Of Phmentioning
confidence: 99%